Correlation relationship between maximal alactate work efficiency and athletic performance of highly-skilled female racing skiers at stages of Olympic training cycle - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V.; Novikova, N. B. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to identify the dynamics of correlation relationship between maximal alactate work efficiency and athletic performance of highly-skilled female racing skiers in individual sprint skiing at different stages of the annual and Olympic training cycles.